PENYELESAIAN SENGKETA GANTI RUGI LAHAN SERTIFIKAT HAK MILIK NOMOR 00471 PADA PTOYEK JALAN TOL PEKANBARU-PANGKALAN - Meltiani Br. Pardede; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the implementation of the use of land in Indonesia regulated in Article 33paragraph (3) of the 1945 Law, the article explains that everything regarding naturalresources including land that is within the territory of Indonesia means that it is controlled,regulated, managed and distributed by the state or government with all its managinginstitutions to be used for the prosperity or welfare of the Indonesian people as a whole.The research method used in this study is the Sociological method. The research wasconducted in Silam Village, Kuok sub-district, Kampar Regency and the Kampar RegencyNational Land Agency Office which were the objects of this research case. Then thepopulation and sample are several parties related to the problem under study, as well as datasources used primary data and secondary data. Data collection techniques in this study wereinterviews and literature review.The conclusions obtained from the results of this study are First, based on the factorscausing the delay in compensation costs on the land title Certificate No. 00471 for thePekanbaru-Pangkalan toll road project, it is hoped that the National Land Agency is theagency authorized for land acquisition, so checking and determining the location must becarried out with accuracy regarding the data so as not to cause problems. Second, it is hopedthat in land acquisitions by determining for the public interest, including the interests of thenation and the state as well as the common interests of the people, land rights can berevoked, by providing appropriate compensation according to the manner regulated by law.Keywords: Dispute Resolution, Compensation, Non Litigation.